Evaluation of different peatland management scenarios to reduce GHG emissions from fires: a case study in tropical peatlands in Ogan Komering Ilir, Indonesia - Rodríguez Vásquez, María José (2020)
UCR::Rectoría::Oficina de Asuntos Internacionales y Cooperación Externa (OAICE)